(untitled) (Journal of the College of Basic Education, 2022)
The television document is no longer the images recorded on a magnetic tape or on a computer memory or A CD in order to achieve the immediate goal of achieving a scoop in the field of news It went far beyond that to become the new photographic memory of the world, and with the increasing interest in television documents. These documents began to play an important role in the consolidation of the events of the feature films, whose story is largely based on directly or indirectly, on a specific factual event that took place during the occurrence of the film’s story or that the film itself He talks about that realistic event, which made the use and employment of the television document in favor of deepening